The Relationship between Neutrophil-to-Lymphocyte Ratio and Intracerebral Hemorrhage in Type 2 Diabetes Mellitus - Luo, Peng; Li, Rui; Yu, Siyuan; Xu, Tingting; Yue, Shufan; Ji, Yongli; Chen, Xin; Xie, Haiting (Journal of stroke and cerebrovascular diseases, 2017)
Chronic systematic inflammation has been suggested to be associated with the occurrence and development of cardiovascular events. Low-grade systematic inflammation persists in type 2 diabetes mellitus (T2DM) patients. In addition, the risk of cerebral hemorrhage in these patients is increased compared with non-diabetic patients. Neutrophil-to-lymphocyte ratio (NLR) is the ratio derived by dividing the neutrophil count with the lymphocyte count from a peripheral blood sample. This study aimed to explore the relation between NLR and cerebral hemorrhage, and to prove that NLR is an independent risk factor of cerebral hemorrhage in T2DM patients. In total, 429 cases of T2DM patients were included. The patients were divided into two groups depending on the presence of cerebral hemorrhage: the cerebral hemorrhage group (n = 87) and the control group (n = 342). Based on clinical and laboratory data of diabetes diagnosis, this article investigates the relationship between NLR and the risk of cerebral hemorrhage. Increase in NLR was positively correlated with the incidence of cerebral hemorrhage in T2DM patients and might serve as an independent risk factor of cerebral hemorrhage in T2DM patients (OR: 4.451, 95% CI: 2.582-7.672). NLR >2.58 might be useful in predicting the threshold value of cerebral hemorrhage risk in newly diagnosed T2DM patients (area under the curve: .72, 95% CI: .659-.780, P < .001) As an indicator of the degree of systematic inflammation, NLR is an independent risk factor of cerebral hemorrhage in T2DM patients.